2014
DOI: 10.4236/ojf.2014.42019
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Diversity of Rhizobial Populations Associated with <i>Acacia senegal</i> (L.) Willd. Provenances in Senegalese Arid and Semiarid Regions

Abstract: Distribution and diversity of rhizobial strains associated with Acacia senegal (L.) Willd. in relation to seed provenances in soils from arid (Dahra) and semiarid (Goudiry) zones of Senegal were investigated. PCR-RFLP performed on 16S-23S rDNA intergenic spacer (IGS) of nodule crude extracts revealed a high genetic diversity of rhizobial strains, which was higher in the semiarid region than in the arid region. The distribution of rhizobial populations was influenced by soil physical and chemical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…About 37.5% of the strains grew in all the heavy metals at the concentrations used in this study, a characteristics of other Vachellia rhizobia (Bakhoum et al 2014) (Table 3). The soil from which the rhizobia isolates were extracted did not influence the clustering of the isolates in relation to their ability to tolerate heavy metals.…”
Section: Effect Of Toxicity Of Heavy Metals To Rhizobia Growthmentioning
confidence: 69%
“…About 37.5% of the strains grew in all the heavy metals at the concentrations used in this study, a characteristics of other Vachellia rhizobia (Bakhoum et al 2014) (Table 3). The soil from which the rhizobia isolates were extracted did not influence the clustering of the isolates in relation to their ability to tolerate heavy metals.…”
Section: Effect Of Toxicity Of Heavy Metals To Rhizobia Growthmentioning
confidence: 69%
“…The data suggested that the rhizobia that associate with S. senegal are characterized by the soil from which they were collected, and studies performed in Senegal support these conclusions. Further support comes from investigations where the diversity of nodulating bacteria associated with S. senegal was found to be high when the soil physical and chemical parameters were favorable (Bakhoum et al, 2014). These authors also reported that nodulating bacteria for S. senegal appeared to be selected by seed provenance.…”
Section: Microsymbionts Associated With S Senegalmentioning
confidence: 93%
“…Studies performed in Senegal have shown that even though S. senegal is nodulated by the genus Rhizobium, its main symbionts are strains phylogeneticaly related to Mesorhizobium plurifarium (Bakhoum et al, 2014;Fall et al, 2008;Sarr et al, 2005b,a). However, some of the strains that nodulate S. senegal and previously described as M. plurifarium belong to a new species .…”
Section: Microsymbionts Associated With S Senegalmentioning
confidence: 99%
See 1 more Smart Citation
“…De ce fait, il serait souhaitable que d'autres systèmes de culture des plantes soient essayés. Sachant que la distribution des populations rhizobiennes est corrélée aux caractéristiques physicochimiques des sols (Bakhoum et al, 2017), il est souhaitable de trouver une nouvelle méthode qui consiste à enrichir les dilutions de sols avant de les inoculer.…”
Section: Dénombrement De Rhizobium Sp Cicer Dans Le Solunclassified